Emerging Sounds Through Implicit Cooperation: A Novel Model for Dynamic Music Generation - Escarce Junior, Mário; Rossmann Martins, Georgia; Soriano Marcolino, Leandro; Tavares dos Passos, Yuri (Proceedings of the AAAI Conference on Artificial Intelligence and Interactive Digital Entertainment, 2017)
Normally agents cooperate when they have a joint goal or are able to get a higher payoff by doing so. We present a new perspective, where an agent cooperates with another without an explicit intention. We study this perspective in the context of Art Games, by introducing a novel algorithm where a human agent cooperates with a video game system in generating music in an emergent fashion, without needing awareness that he/she is doing so. We present a theoretical analysis of our system, and preliminary experiments with human subjects.